Strength and conditioning for a science of human movement - Maximizing athletic performance: Observations on periodization and variation - Hoffman, J. R. (EWF Scientific Magazine, 2016)
In the past half-century a number of studies have examined how manipulation of intensity and volume of training can influence improvements in strength and power. Early investigations focused on examining an optimal training intensity (i.e. load) that should be used to maximize strength gains (Berger, 1962; O`Shea, 1966). Subsequent studies though have suggested that when training intensity and volume are altered within a training cycle, that strength performance can be enhanced to a significantly greater extent than when these training variables are maintained consistent during the training period (Harris et al., 2000; Kraemer, 1997; Kraemer et al., 2003; Marx et al., 2001; Stone et al., 1982; 2000; Willoughby et al., 1993). The steplike alteration of training intensity and volume is commonly referred to as the traditional model of periodization (Baker et al., 1994; Hoffman, 2002; Rhea et al., 2002). It is also referred to as linear or block periodization in which each phase of the training program emphasizes a specific training goal (i.e., hypertrophy, strength or power) (Bartolomei et al., 2014). Linear or block periodization is typically characterized by an inverse relationship between intensity and volume of training. During the beginning of the training cycle training volume is high and training intensity is low. As the training cycle progresses training intensity will increase, while training volume declines. This is typical for the training program emphasizing increases in strength performance. However, for many athletes the goal may be to simultaneously emphasize both